Could low fat mediterranean diet improves competitive anxiety in young sailors?: cross-sectional study according to the STROBE statement - Martínez-Rodríguez, A.; Chicoy-García, I.; Leyva-Vela, B.; Martínez-Hernández, M.; Manzanares Serrano, A. (Cuadernos de Psicología del Deporte, 2017)
In dinghy sailing, there are many factors all of which affect to sailor performance: experience, training, nutrition and psychological condition. e main aim of this report was to know sailor’s anxiety levels according to eating habits, nutritional condition, training, experience and type of vessel. 77 Laser (4.7 and Radial) and 470 sailors lled up CSAI-2 and PREDIMED questionnaires to determine competitive state anxiety and low fat diet adherence. They showed higher BMI the sailors with higher low fat diet adherence, higher experience, higher ranking position and Radial’s sailors. Under-16 sailors showed less competitive anxiety. Overweight sailor got less cognitive anxiety. Sailors who trained more times per week got best results. Sailors with higher BMI will get best results with strong wind because they will keep the boat horizontal more easily. Radial’s sailors have higher BMI due to their age. Under-16 sailors show less competitive anxiety due to lower demand for results. Overweight sailor show less cognitive anxiety due to lower expectations. Sailors who train more times per week get best results. Low fat Mediterranean diet not seem conditioned competitive anxiety in sailors. Sailing performance seems to be conditioned by sailor weight, wind conditions, training frequency and experience.